Teaching innovation faced the challenges of the limitations of the covid-19 pandemic for industrial and laboral sociology - Tamboleo García, Rubén (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
We analyze the differences between carrying out a traditional teaching in which we fill our class hours with master sessions and between an innovative teaching according to the regulations and indications of the Bologna plan in which we must have around 50% of the sessions as practices. that will be evaluated according to what is established at the beginning of the subject. In this work we compare two subjects: one with traditional teaching and one with innovative teaching and our objective is to measure if one of the two generates more adherence, more presence in class and more interaction with the teacher. Thus, we establish a comparative methodology between the two and examine those indicators. With these results, we can reach some conclusions and open a discussion for future steps and improvements in face-to-face University teaching.